Astrology and Astrologers during the first and second Abbasid periods (132 - 334 AH/ 750 - 946 AD) - abdennouz, fatiha (The Algerian Historical Journal, 2026)
This article examines the status of Astrology and Astrologers during the first and second Abbasid periods (132 - 334 AH/ 750 - 946 AD). It explores the activities of Abbasid astrologers and their contributions to the development of this “science of the stars” Sinaeat Eilm Alnujum. The article begins by defining astrology in Arab and Western contexts and then traces its origins in Indian, Persian, and Greek sources, focusing on its transmission to the Arab- Islamic world, particularly during the early Abbasid period. It analyzes the Abbasid caliphs role in astrology’s development and highlights key astrologers and their positions during the first and second Abbasid periods.